GC/MS PROFILING, ANTIBACTERIAL AND ATOMIC FORCE MICROSCOPIC STUDY OF BACTERIAL CELL MEMBRANE AFFECTED BY FARSETIA HELIOPHILA BARK EXTRACT ALONG WITH WOUND HEALING ACTIVITY - S. Burki; Z. G. Burki; Mehjabeen; M. Khan; I. Ahmed; S. Ali (Journal of Animal and Plant Sciences, 2022)
The aim of the study was to evaluate phytochemically, biologically and pharmacologically Farsetia heliophila (F. heliophila) using in vivo wound healing technique. Phytochemically, F. heliophila positive test for tannins, saponins, flavonoides, triterpenoids and alkaloids. The chemical composition of F. heliophila evaluated through gas chromatography (GC), gas chromatography/mass spectroscopy (GC/MS) and Fourier transformed infra-red (FTIR) reveled that F. heliophila contain important bioactive compounds like barrigenol R1, ethyl iso-allocholate, lupeol acetate, isorhamnetin, α-amyrine, α-tocopherol, l-(+)-ascorbic acid 2,6-dihexadecanoate, ascorbyl palmitate, 2-pyrazolin-5-one, 3,4,4-trimethyl- isoquercetin, pyrimidine, indole and cyclolaudenol. The crude extract was further evaluated for antibacterial activity, (AFM) study of extract treated bacterial cells, acute oral toxicity and in vivo wound healing potential. The MIC50 values of F. heliophila extract against B. subitils, S. typhi E. coli and P. aeruginosa were 25, 50, 75 and 100 µg/mL at (p<0.01) and (p<0.05). The AFM images showed that the cell membrane of B. subitils, S. typhi and E. coli were significantly damaged with cytoplasm leaked from the bacterial cell. P. aeruginosa cell membrane was partially damaged. The extract did not show any acute toxicity at higher dose of 2000, 3000 and 5000 mg/kg. The results of wound healing capabilities showed that the wounds were significantly healed in animals treated with F. heliophila extract at 10 and 15 % ointment dose at (p<0.01 and p<0.001). The epithelialization process was also accelerated at 10 an 15 % dose of F. heliophila extract ointment and took 20.4±2.0 and18.5±1.2 days for complete wound healing. The results of this study provide scientific support for alternative use of F. heliophila as a therapeutic agent in the treatment of skin wounds and infections.
Keywords: Farsetia heliophila; GC/MS; Antibacterial; AFM; Acute toxicity; Wound healing